Assessment of colorectal cancer awareness in patients admitted to the general surgery outpatient clinic - İdiz, Cemile and Cakir, Coskun and Kegin, Murat and Ulusoy, Abdulhakim (The European Research Journal, 2021)
Objectives: Colorectal cancer could be prevented with some basic lifestyle modifications.In this study we query the awareness of the participants about colorectal cancer who visit the general surgery outpatients clinic. Methods: A questionnaire consisting of 13 questions was applied to the participants as well as demographic data. Differences in awareness of screening and risk factors were sub-grouped according to age, BMI, education, employment status, monthly income, marital status, status of first-degree relative colorectal cancer, smoking-alcohol use status and exercise status. Results: The most known screening method was colonoscopy with 73.6%, while the least known screening method was sigmoidoscopy with 13.4%. Also, the best known risk factor was smoking with 67.4%, while the least known risk factor was type 2 diabetes with 29.8%. In our study, those over 45 years of age, having higher education, working, having more monthly income, having a family history of colorectal cancer and exercising regularly had more awareness about colorectal cancer screening and risk factors. Conclusions: Our study had high levels of awareness compared to developing countries, however, awareness levels are not high enough and it is possible to increase these rates by educating the patients on cancer awareness.